2010
DOI: 10.1007/s13213-009-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of 10-(diphenylmethylene)-4-azatricyclo[5.2.1.02,6]dec-8-ene-3,5-dione derivatives

Abstract: Antibacterial and antifungal activity of 10-(diphenylmethylene)-4-azatricyclo[5.2.1.0 2,6 ]dec-8-ene-3,5-dione derivatives were examined by the disk diffusion method (growth inhibition zone diameter in agar medium). The minimal inhibitory concentrations (MICs) for the most active agents were determined. Title compounds were also evaluated in vitro against HIV-1 virus and their cytotoxicity was determined. Aminoalkanol derivatives exhibited activity against the majority of microorganisms studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Activity of S-substituted derivatives of bistriazolethione 13 depends on the nature of the substituent. The free radical scavenging activity of compounds containing alkyl groups (15)(16)(17)(18)(19)(20) was approx. 50 %, whereas that of 22 containing benzyl group was only 3.61 %.…”
Section: Evaluation Of Antioxidative Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Activity of S-substituted derivatives of bistriazolethione 13 depends on the nature of the substituent. The free radical scavenging activity of compounds containing alkyl groups (15)(16)(17)(18)(19)(20) was approx. 50 %, whereas that of 22 containing benzyl group was only 3.61 %.…”
Section: Evaluation Of Antioxidative Propertiesmentioning
confidence: 99%
“…1,2,4-Triazole scaffold is yet another important pharmacophore since compounds bearing this moiety have been shown to display anti-inflammatory and analgesic [17], antitumor [18], antioxidative [19], antibacterial [13,14,20], and antifungal [21] properties. 1,2,4-Triazole derivatives, e.g., flucarbazone and amicarbazone, are used as herbicides [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,8-diazabicyclo-[3.2.1]-octane analogues and 4-azatricyclo-[5.2.2.02.6]-undecane-3,5,8-triones derivatives have been investigated as potential agents for the inhibitory effects of anti-proliferation and HIV-1 multiplication in MT-4 cells respectively [15]. Azatricyclo-dec-8-ene-3,5-dione derivatives have antibacterial and anti-fungal activities with other important biological activities [16]. Grunewald et al [17] reported the medicinal chemistry of annulenes and related compounds like, 11 3,5,7,9-pentanene as antiviral agents.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies (Stefańska et al, 2009;Stefańska et al, 2010), we presented strongly hydrophobic aromatic compounds with nitrogen-containing imide part that have shown good antimicrobial activity. This study reports biological activity of compounds purposely designed to combine the heterocyclic sulphur containing ring of 1,4-dithiine with aminoalkanol or alkyl linker bearing different substituents.…”
Section: Introductionmentioning
confidence: 99%